The Impact of Maternal Supplementation of Fish Oil and/or Probiotics During Pregnancy on the Serum Metabolomic Profile From Infancy to Childhood: Secondary Analysis of a Randomized Placebo-Controlled Trial - Houttu, Veera; Mongad, Dattatray; Houttu, Noora; Saros, Lotta; Zhang, Chunpeng; Viitaharju, Jenni; Vahlberg, Tero; Lahti, Leo; Laitinen, Kirsi (Elsevier BV, 2026)
Background
Supplementation with probiotics and fish oil may modify circulating serum metabolites, but the extent to which their impacts can be transferred from mother to child is unknown.
Objectives
To investigate the impact of perinatal exposure to fish oil and/or probiotics on serum metabolomic profile in early childhood.
Methods
Children (n = 300) of pregnant females receiving fish oil+placebo, probiotics+placebo, fish oil+probiotics, or placebo+placebo [fish oil: 1.9-g docosahexaenoic acid and 0.2-g eicosapentaenoic acid; probiotics: Lacticaseibacillus rhamnosus HN001 and Bifidobacterium animalis subsp. lactis 420] from early pregnancy to 6-mo postpartum were observed until 5–6 y of age. Serum metabolomic profiles were analyzed using nuclear magnetic resonance metabolomics. The intervention’s impact on the overall metabolomic profile was assessed using permutation analysis of variance with multi-omics factor analysis utilized to infer latent factors that capture main sources of variability within each group, followed by a univariate comparison between the intervention groups at each age. The time effect was analyzed using a mixed model.
Results
We observed significant differences in the concentrations of fatty acids and lipoproteins at 6 months across the intervention groups (false discovery rate < 0.05). The main effects included higher serum concentration of docosahexaenoic acid and n–3 fatty acids, a higher ratio of n–3/n–6 fatty acids in fish oil+placebo and fish oil+probiotics groups compared with placebo+placebo, along with higher concentrations of lipids and cholesterol derivatives in very large high-density lipoproteins. At 6 mo, there were no significant differences in these metabolites for the probiotics+placebo group compared to placebo+placebo. At 1, 2, and 5–6 y, a total of 24 metabolites were affected by the intervention (non-significant after multiple correction).
Conclusions
Maternal intervention with fish oil alone and in combination with probiotics induces alterations in the metabolic profile at 6 mo of age, as demonstrated by increased circulating n–3 fatty acids and lipids in high-density lipoproteins.